Guidelines for percutaneous endoscopic spinal surgery - Birkenmaier, Christof; Chiu, John C.; Fontanella, Andrea; Leu, Hansjörg F.; Ruetten, Sebastian (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Randomized controlled trials have demonstrated equal effectiveness of the endoscopic procedures compared to the microsurgical reference procedures in cervical as well as in lumbar applications. Some of these studies also showed lower complication rates with endoscopy and none had higher complication rates with endoscopy. In these trials, spinal endoscopy generated less postoperative pain and faster rehabilitation than the microsurgical procedures. However, all these trials with one exception were performed by the same team of highly experienced endoscopic spinal surgeons. It is conceivable, that surgeons with less experience may not necessarily be able to achieve the same results. RCTs from other groups will have to prove or disprove this assumption. Sofar, no long-lasting advantages of endoscopic spine surgery over the microsurgical technique have been demonstrated. There is some experimental evidence that the effects of reduced access trauma can be measured, but interestingly, there seems to be no advantage of using a microtubular retractor system over standard microsuraical techniaue and instruments.